Genomic Characterization of Campylobacter jejuni Adapted to the Guinea Pig (Cavia porcellus) Host - Parker, Craig T.; Cooper, Kerry K.; Schiaffino, Francesca; Miller, William G.; Huynh, Steven; Gray, Hannah K.; Olortegui, Maribel Paredes; Bardales, Paul Garcia; Trigoso, Dixner Rengifo; Penataro-Yori, Pablo; Kosek, Margaret N. (Frontiers in Cellular and Infection Microbiology, 2021)
Campylobacter jejuni is the leading bacterial cause of gastroenteritis worldwide with excessive incidence in low-and middle-income countries (LMIC). During a survey for C. jejuni from putative animal hosts in a town in the Peruvian Amazon, we were able to isolate and whole genome sequence two C. jejuni strains from domesticated guinea pigs (Cavia porcellus). The C. jejuni isolated from guinea pigs had a novel multilocus sequence type that shared some alleles with other C. jejuni collected from guinea pigs. Average nucleotide identity and phylogenetic analysis with a collection of C. jejuni subsp. jejuni and C. jejuni subsp. doylei suggest that the guinea pig isolates are distinct. Genomic comparisons demonstrated gene gain and loss that could be associated with guinea pig host specialization related to guinea pig diet, anatomy, and physiology including the deletion of genes involved with selenium metabolism, including genes encoding the selenocysteine insertion machinery and selenocysteine-containing proteins.